Pendampingan kegiatan literasi membaca dengan memanfaatkan aplikasi whatsapp di SD Negeri 2 Lalombaa Kabupaten Kolaka - Ernawati Ernawati; Tri Maniarta Sari; Nurul Haeniah; Susi Astianti; Agus Nasir (Universitas Sarjanawiyata Tamansiswa, 2022)
SD Negeri 2 Lalombaa is one of the elementary schools in Kolaka and has become a partner in this PkM, where the literacy activities at that school are still not optimally implemented, especially during the COVID-19 pandemic. So it causes students’ reading interests to be lower. The PkM team provides a solution to school partners, namely the reading literacy movement, by utilizing WhatsApp as a medium in post-pandemic literacy activities. This PkM activity was carried out in June–August 2022, carried out offline and online with the stages of activities starting with socialization; procurement of reading materials; forming and repairing reading corners; various reading activities including: making book summaries; story telling; and educational games. The target of the activity is grade 4 and grade 5 students by involving teachers. The results of the descriptive analysis (questionnaire) showed that students' reading interest before the implementation of PkM activities was in the low category (average score of 59.0), while after the implementation were in the medium category (average score of 81.11), and the results of paired sample t-test obtained a p value (sig.) of 0.000 (0.05), so it was stated that the PkM activities carried out succeeded in increasing students' reading interest. Furthermore, teachers who gave a positive response of 83.33% and parents of 82.14% (meaning above 80%). Thus, it was concluded that the mentoring of reading literacy activities by utilizing the WhatsApp application carried out by the PkM team was successfully implemented and could be applied to increase students' reading interest.